Effect of the presence of the pericarp on the chemical composition and sensorial attributes of arabica coffee - Shuler, Joel Douglas (2017)
The purpose of this study was to gain further insight into how the natural coffee flavor profile develops during processing. This was done by analyzing how the presence of the pericarp, removed at different times throughout the coffee drying, affected the chemical composition of green coffee beans and the resulting flavor in the coffee beverage. Coffee fruit was selectively harvested from a highaltitude coffee field outside of Cristina, Minas Gerais, Brazil, picking only ripe fruit. This fruit was subjected to hydraulic separation of floaters and then further hand selection to ensure the lot contained only ripe, undamaged coffee fruit. Part of the lot was separated and processed as a wet process coffee. It was pulped, removing the epicarp and part of the mesocarp, and manually washed with fresh water to remove any remaining mesocarp (mucilage). The remaining fresh fruit was divided into 5 treatments, a treatment being defined by the wet basis moisture content level at which its pericarp would be removed (32 ± 2 °C, 28 ± 2 °C, 22± 2 °C, 18± 2 °C and 11± 2 °C). All samples were dried at a temperature of 37 ± 2 °C with constant rotation during the drying, first every half hour, then every hour once 32% moisture content was reached, and then every two hours once 18% moisture content was reached. After one month of storage, the coffee was hulled and then subjected to chemical and sensory analysis. The chemical analysis comprised bioactive compounds (trigonelline, caffeine, and total chlorogenic acids), low molecular weight carbohydrates, fatty acids, and organic acids. The results yielded statistically significant differences in levels of trigonelline, quinic acid, and malic acid. Perhaps as important, the results showed no difference in either the levels of fatty acids or low molecular weight carbohydrates. The overall scores for the sensory analysis were not statistically different; however, no taster (cupper) identified the wet process coffee as having a “natural flavor profile.”